Activating Nrf2 signalling alleviates osteoarthritis development by inhibiting inflammasome activation. Issue 22 (23rd September 2020) - Yan, Zijian; Qi, Weihui; Zhan, Jingdi; Lin, Zeng; Lin, Jian; Xue, Xinghe; Pan, Xiaoyun; Zhou, Yulong
Abstract: Osteoarthritis (OA), which is characterized by proliferation of subchondral bone and the degeneration of articular cartilage, is the most prevalent human arthritis. Nod‐like receptor pyrin domain 3 (NLRP3) inflammasome is a hot spot in recent year and has been reported to be associated with OA synovial inflammation. However, there are few studies on NLRP3 inflammasome in chondrocyte. Licochalcone A (Lico A), a compound extracted from Glycyrrhiza species, has various biological effects such as anti‐inflammation, anti‐apoptotic, anti‐cancer and anti‐oxidation. In this study, we investigated the protective effect of Lico A on chondrocytes stimulated by lipopolysaccharide (LPS) and surgically induced OA models. In vitro, Lico A could reduce the expression of NLRP3, apoptosis‐associated speck‐like protein (ASC), Gasdermin D (GSDMD), caspase‐1, interleukin‐1beta (IL‐1β) and IL‐18, which indicated that Lico A attenuates LPS‐induced chondrocytes pyroptosis. In addition, Lico A ameliorates the degradation of extracellular matrix (ECM) by enhancing the expression of aggrecan and collagen‐II. Meanwhile, we found that Lico A inhibits NLRP3 inflammasome via nuclear factor erythroid‐2‐related factor 2 (Nrf2)/haeme oxygenase‐1(HO‐1)/nuclear factor kappa‐B (NF‐κB) axis. And the Nrf2 small interfering RNA (siRNA) could reverse the anti‐pyroptosis effects of Lico A in mouse OA chondrocytes. In vivo, Lico A mitigates progression OA in a mouse model and reduces OA Research Society International (OARSI) scores. Thus, Lico A may have therapeutic potential in OA.